Facts on File world news digest CD-ROM - World News Digest, Inc.; EBSCO Publishing (Firm) (New York : Facts On File)
Facts On File world news digest CD-ROM is a universal reference system that puts all the basic facts of U.S. and world news at your fingertips.
Description based on: 1995 no. 1; title from container.
Keywords: World politics -- 20th Century -- Periodicals; Foreign news -- Periodicals; Geography -- Periodicals